2010
DOI: 10.1002/hed.21615
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical management of oropharyngeal, laryngeal, and hypopharyngeal cancer: The Fox Chase Cancer Center experience

Abstract: The survival of patients with oropharyngeal and hypopharyngeal cancers treated at our institution has improved over the last 15 years, which is likely related to changes in treatment and tumor biology. The improvement was not observed in patients with laryngeal cancer. A subset of patients with oropharyngeal cancer remain subject to local failure and disease-related death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Twenty‐two articles were selected for inclusion and analysis in the study (Table ) . The studies reported on 1105 patients, a mean of 50 patients (range, 5–163) per study, published between 1976 and 2014.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐two articles were selected for inclusion and analysis in the study (Table ) . The studies reported on 1105 patients, a mean of 50 patients (range, 5–163) per study, published between 1976 and 2014.…”
Section: Resultsmentioning
confidence: 99%
“…The differences in OS and progression‐free survival were stark: HRs for death and relapse or death were 0.29 and 0.33, respectively, for patients in the low‐risk group compared to the high‐risk group . The profound effect of HPV on oropharyngeal SCC outcomes has been confirmed in multiple retrospective single institution and nationwide database analyses . Together, these data have led to increased optimism regarding the future of clinical outcomes for patients with oropharyngeal SCC.…”
Section: Discussionmentioning
confidence: 97%
“…3 The profound effect of HPV on oropharyngeal SCC outcomes has been confirmed in multiple retrospective single institution and nationwide database analyses. [2][3][4]6,8,[10][11][12][13] Together, these data have led to increased optimism regarding the future of clinical outcomes for patients with oropharyngeal SCC.…”
Section: Discussionmentioning
confidence: 99%